Examining the Educational Gap for Children with ADHD and Subthreshold ADHD. Issue 2 (January 2022) - Zendarski, Nardia; Guo, Shuaijun; Sciberras, Emma; Efron, Daryl; Quach, Jon; Winter, Leanne; Bisset, Matthew; Middeldorp, Christel M.; Coghill, David
Objective: The present study examined the impact of Attention Deficit Hyperactivity Disorder (ADHD) on core educational outcomes in two large community cohorts of Australian school children. Method: Academic (reading and numeracy) and non-academic (school engagement, attendance, peer victimization, and parental expectations) outcomes were compared between children with ADHD, subthreshold ADHD, and controls when children were in grade 5 (M age = 10.5). Data were drawn from the Longitudinal Study of Australian Children birth cohort (LSAC; N  = 3, 540) and the Children's Attention Project (CAP; N  = 356). Results: Both subthreshold ADHD and ADHD groups had poorer outcomes on all measures, with medium effects sizes. Differences were not evident between subthreshold ADHD and ADHD groups. Conclusions: Educational outcomes examined in this study highlight the educational risk for upperprimary school children with ADHD or subthreshold ADHD, in comparison to their peers. Monitoring these outcomes is necessary to inform policy, practice, and intervention.